Integrity of the core mitochondrial RNA-binding complex 1 is vital for trypanosome RNA editing - Huang, Zhenqiu; Faktorová, Drahomíra; Křížová, Adéla; Kafková, Lucie; Read, Laurie K; Lukeš, Julius; Hashimi, Hassan (RNA (New York, N.Y.), 2015)
Trypanosoma brucei is the causative agent of the human and veterinarian diseases African sleeping sickness and nagana. A majority of its mitochondrial-encoded transcripts undergo RNA editing, an essential process of post-transcriptional uridine insertion and deletion to produce translatable mRNA. Besides the well-characterized RNA editing core complex, the mitochondrial RNA-binding 1 (MRB1) complex is one of the key players. It comprises a core complex of about six proteins, guide RNA-associated proteins (GAPs) 1/2, which form a heterotetramer that binds and stabilizes gRNAs, plus MRB5390, MRB3010, and MRB11870, which play roles in initial stages of RNA editing, presumably guided by the first gRNA:mRNA duplex in the case of the latter two proteins. To better understand all functions of the MRB1 complex, we performed a functional analysis of the MRB8620 core subunit, the only one not characterized so far. Here we show that MRB8620 plays a role in RNA editing in both procyclic and bloodstream stages of T. brucei, which reside in the tsetse fly vector and mammalian circulatory system, respectively. While RNAi silencing of MRB8620 does not affect procyclic T. brucei fitness when grown in glucose-containing media, it is somewhat compromised in cells grown in the absence of this carbon source. MRB8620 is crucial for integrity of the MRB1 core, such as its association with GAP1/2, which presumably acts to deliver gRNAs to this complex. In contrast, GAP1/2 is not required for the fabrication of the MRB1 core. Disruption of the MRB1 core assembly is followed by the accumulation of mRNAs associated with GAP1/2.
Keywords: mitochondrion; Cell Line; messenger RNA; RNA, Messenger; mitochondrie; buněčné linie; RNA Editing; trypanosome; editace RNA; mitochondriální proteiny; Mitochondria; RNA editing; protozoální proteiny; Protozoan Proteins; Trypanosoma brucei brucei; Mitochondrial Proteins